Impact of moderate and late preterm birth on neurodevelopment, brain development and respiratory health at school age: protocol for a longitudinal cohort study (LaPrem study). Issue 1 (31st January 2021) - Cheong, Jeanie; Cameron, Kate Lillian Iona; Thompson, Deanne; Anderson, Peter J; Ranganathan, Sarath; Clark, Ross; Mentiplay, Benjamin; Burnett, Alice; Lee, Katherine; Doyle, Lex William; Spittle, Alicia J
Abstract : Introduction: Children born moderate to late preterm (MLP, 32–36 weeks' gestation) account for approximately 85% of all preterm births globally. Compared with children born at term, children born MLP are at increased risk of poor neurodevelopmental outcomes. Despite making up the largest group of preterm children, developmental outcomes of children born MLP are less well studied than in other preterm groups. This study aimed to (1) compare neurodevelopmental, respiratory health and brain magnetic resonance imaging (MRI) outcomes between children born MLP and term at 9 years of age; (2) examine the differences in brain growth trajectory from infancy to 9 years between children born MLP and term; and in children born MLP; (3) examine the relationship between brain development and neurodevelopment at 9 years; and (4) identify risk factors for poorer outcomes at 9 years. Methods and analysis: The "LaPrem" (La te Pre term M RI Study) study is a longitudinal cohort study of children born MLP and term controls, born at the Royal Women's Hospital in Melbourne, Australia, between 2010 and 2013. Participants were recruited in the neonatal period and were previously followed up at 2 and 5 years. This 9-year school-age follow-up includes neuropsychology, motor and physical activities, and lung function assessments, as well as brain MRI. Outcomes at 9 years will be compared between birth groups using linear and logistic regressions. Trajectories of brain development will be compared between birth groups using mixed effects models. The relationships between MRI and neurodevelopmental outcomes, as well as other early predictors of poor 9-year outcomes, will be explored using linear and logistic regression. Ethics and dissemination: This study was approved by the human research ethics committee at the Royal Children's Hospital, Melbourne, Australia. Study outcomes will be disseminated through peer-reviewed publications, conference presentations and social media.